APPLYING DRAMA TECHNIQUES IN TEACHING ENGLISH IN IRAN - BAHRAM MOGHADDAS (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This paper concentrates on the teaching of drama, its advantages to language teaching and learning, and how to utilize drama in English classrooms. It concludes with some diverse activities for contributing English learners in India. Drama here means any practical and educational activity which stimulates the use of language in everyday life and involves some amount of imaginary situation(Holden,1981).Some benefits of using drama in language learning are enhancing learner’s autonomy and responsibility over their own learning, providing a stress free atmosphere to learn the language, putting new vocabularies and expressions in context, helping to get acceptable pronunciation and intonation, proper understanding of foreign language culture and building up learners’ confidence to speak in public. These drama techniques have been utilized by some English teachers at two different high schools in Ilam Province in Iran which amazingly turned the English classrooms to active participants, reduced the academic stress and provided natural context for learning. Although text books prepared the learners with language, drama activities prepared the learners to participate with real communication and paved the way for the learners to experiment personal language learning.